(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
This article discusses the features of the style and techniques of the Russian writer Viktor Olegovich Pelevin. He is one of the most popular, read and discussed writers of contemporary Russia. He graduated from the Literary Institute, is literate, well-read and, of course, talented.In his works, he raises many eternal questions of mankind. The meaning of human life? What is consciousness? How is the world? Pelevin’s work is not included in the framework of ordinary creativity, so it is difficult to attribute it to any school. In his works one can find features of surrealism, postmodernism, symbolism, fantasy. He himself refers to the school of pop art.